Factors Influencing the Interest of MSME Actors in the Implementation of Mobile-Based Accounting Applications in Bengkalis Regency - Annisa Rezki Susanti; N. Nasrizal; Novita Indrawati (Manunggal Halim Jaya, 2026)
The increase in the number of Micro, Small, and Medium Enterprises (MSMEs) is driven by personal economic pressures such as layoffs, government support through programs such as KUR and PEN as well as easy access to technology, and changes in market needs that utilize digitalization and the quality of local products. The MSME sector is also a major pillar of the economy because it absorbs a large workforce and contributes significantly to GDP. The interest of MSME actors in using mobile-based accounting applications can be explained by the UTAUT theory. The sample in this study was 83 MSMEs in Bengkalis Regency, which are categorized as small and medium enterprises. The data collection technique was carried out through the distribution of closed questionnaires designed based on indicators. Data analysis used Structural Equation Modeling (SEM) to test direct and indirect relationships between variables. The results showed that performance expectations significantly influenced the interest of MSME actors. Effort expectations significantly influenced the interest of MSME actors. Social factors significantly influenced the interest of MSME actors. Facilitating conditions did not significantly influence the interest of MSME actors. Technology anxiety significantly influenced the interest of MSME actors. Risk perception does not have a significant effect on the interest of MSME actors.